KEPEMIMPINAN TRANSFORMASIONAL DALAM PENGELOLAAN PROGRAM TAHFIDZ ALQURAN DI PKBM HARAPAN BANGSA KABUPATEN KAMPAR - Anita Gusti Amelia; Said Suhil Achmad; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: The formulation of the problem in this study is who are the people involved in managing the tahfidz Alquran program at PKBM Harapan Bangsa Kampar District? how is the transformational leadership pattern in managing the tahfidz Alquran program at PKBM Harapan Bangsa Kampar District? what is the reason for practicing transformational leadership in the tahfidz Alquran program at PKBM Harapan Bangsa Kampar District? where are the places of implementation of the tahfidz Alquran program at PKBM Harapan Bangsa Kampar District? at what time is used in the tahfidz Alquran program at PKBM Harapan Bangsa Kampar District? This research is a type of descriptive research using a qualitative approach. Data collection is done by observation (observation), documentation, in-depth interviews (indept interviews), data analysis is done by: data reduction (data reduction); data display (data display); and conclusion drawing (conclusion drawing / verifying). This study consists of one variable, namely 4 indicators and 5 sub-indicators, 1) The ideal influence, consisting of sub-indicators showing exemplary, 2) Inspirational motivation, consisting of sub-indicators motivating and appreciating followers, 3) Intellectual stimulation, consisting of sub-indicators have ideas that inspire followers, 4) Individual considerations, consisting of sub-indicators treating followers with respect, and supporting employees' desire to progress and develop. The informants of this study were 3 people consisting of 1 core informant, 1 control informant, and 1 observer informant. The subject of this study was the chairman of the PKBM Harapan Bangsa Kampar District. The results showed that transformational leadership in the management of the Alquran tahfidz program had been implemented by the head of PKBM in accordance with research indicators.Key Words: Transformational Leadership, Management, And The Alquran Tahfidz Program